ЛИБЕРТАРИЗМ И МОРАЛЬ - ДЫШКАНТ, Т. Н. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
На современном этапе развития общества либертарианское направлениестановится доминирующим, не только в области экономики, но и во всех иных сферахобщественной жизни. Поскольку неолибералы доводят свой экономический либерализм доэтической спецификации, возникает потребность анализа практической философиинеолиберализма. Сделан вывод о непоследовательности неолибералов в разработке своейсистемы ценностей, что приводит к исчезновению даже такого основополагающегопонятия как свобода.Ключевые слова: Дишкант Т.М. ЛІБЕРТАРІЗМ І МОРАЛЬ На сучасному етапі розвитку суспільствалібертаріанський напрямок стає домінуючим, не тільки у сфері економіки, але й усіх іншихсферах суспільного життя. У зв’язку з розширенням у неоліберальній теорії економічноголібералізму до етичної специфікації, виникає потреба аналізу її практичної філософії.Зроблено висновок про непослідовність неолібералів при розробці своєї системи цінностей,що призводить до зникнення навіть такого основного поняття як свобода.Ключові слова: лібертарізм, вільний ринок, «негативна» свобода, індивідуалізм.Dyshkant Т. N. LIBERTARISM AND MORAL On the modern stage of development ofsociety libertarian direction becomes dominant, not only in area of economy but also in all otherspheres of public life. As libertarians takes the economic liberalism to ethics specification, thereis the necessity of analysis of practical philosophy of libertarianism. The freedom understood asindependence is the fundamental value of this direction. The open market built on principles ofhonest competition and presence of private property can secure her only. The presence of allabove-mentioned conditions by unintentional way will provide a beneficence societies andspiritual development of man. However by the basic law of the society built exceptionally on amarket exchange without taking into account social component, there is the law of maximalprofits. It is instrumental in that market, all farther walks away from procedural honesty. Thereare processes which are instrumental in elimination, both freedom of markets processes andindividual freedom. A conclusion is thus done about inconsistentness of libertarians indevelopment of the system of values that results in disappearance even such fundamental conceptas freedom.Key words: libertarism, free market, «negative» freedom, individualism.